Character Strengths Predict Subjective Well-Being, Psychological Well-Being, and Psychopathological Symptoms, Over and Above Functional Social Support - Azañedo, Carolina M.; Artola, Teresa; Sastre, Santiago; Alvarado, Jesús M. (Frontiers in Psychology, 2021)
The increasing value of character strengths in the prediction of well-being and psychopathology, after the effects of functional social support and sociodemographic variables are accounted for, is examined. Participants were 1494 Spanish-speaking students between the ages of 18 and 68 (43.3% men and 56.7% women) who completed measures of character strengths, functional social support, subjective well-being, psychological well-being, and symptoms of psychopathology. Functional social support had predictive value in explaining the variability of each component of well-being and psychopathology. Regarding character strengths, theological strengths had the greatest predictive power for life satisfaction (β = .41), positive affect (β = .49), affect balance (β = .45), purpose in life (β = .60), self-acceptance (β = .50), environmental mastery (β = .47), and positive relations with others (β = .25). Emotional strengths made the strongest contribution to the variance explained (β = .41) of autonomy, and intellectual strengths were the strongest predictive variable for personal growth (β = .39). Strengths of restraint had the greatest predictive power for the global severity index of psychopathology (β = -.27).Functional social support and character strengths have strong links to mental health. Positive interventions to develop these variables could contribute to enhance well-being and prevent psychological distress.